The Population and Level of Attack By Pod-Destroying Pests on Several Soybean Varieties as Information for The General Public and Especially Biology Education Students - Nanang Nofriadi (Universitas Muhammadiyah Enrekang, 2023)
Soybean productivity in Jambi province is lower than national soybean productivity. One of the problems in increasing soybean production is pest attacks. This research aims to determine the population and level of attack by pod-destroying pests on several soybean varieties (Glycine max (L) Merrill). The research design used was a Randomized Block Design (RAK) which consisted of 5 treatments with 5 groups. Each treatment was repeated 5 (five) times, so that the total experiment consisted of 25 experimental units. The data analysis technique used is the analysis of variance technique and is followed by Duncan's multiple distance test (DNMRT) at the α = 5% level. The research results show that there are 3 types of pod destroying pests on soybean plants, namely E. zinkenella, R. linearis and N. viridula. Pod sucking attacks were seen in the five soybean varieties, attacks began to appear at 73 days after planting and 80 days after planting. The attack rate was observed at 73 HST with an attack rate of 9.69 - 5.04%. At 80 DAT observations, it was seen that the attack rate was increasing, the highest attack rate occurred on the Anjasmoro variety at 26.22% and the lowest attack rate was on the Jayawijaya variety at 7.43%